Analysis of Puerarin and Chemical Compositions Changes in Kudzu Root during Growth Period - Yiguo Zhao; Mei Xu; Zhinneg You; Dongsheng Li; Mingquan Zhou; Yupeng Zhu; Chao Wang (Journal of Chemistry)
The kudzu root is one of the earliest medicinal plants listed in traditional Chinese medicine. In this paper, chemical compositions changes of kudzu roots from one year old to five years old were analyzed with respect to puerarin, acid-insoluble polysaccharides, acid-soluble polysaccharides, reducing sugar, protein, free amino acids, and lipid. In addition, the puerarin content was determined by high performance liquid chromatography (HPLC) method. The results showed that acid-soluble polysaccharides content of kudzu root increased with each growth period. In contrast, the acid-insoluble polysaccharides decreased significantly. The contents of reducing sugar and puerarin in kudzu root decreased significantly during its growth period. Beyond that, the contents of protein, free amino acids, and lipid in kudzu root ranged from 31.8 to 45.8 g/kg, 2.21 to 4.33 g/kg, and 32.2 to 76.9 g/kg, respectively. The trend of protein content coincided with the total content of free amino acids, in contrast to lipid. This paper provides a set of data and the select of kudzu root for the processing and development of new products of kudzu root.